2022
DOI: 10.3390/nu14122538
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Supplementation, Risk of Cardiovascular Diseases, and Mortality: A Real-World Study of the Korean National Health Insurance Service Data

Abstract: Few studies have investigated the effects of calcium supplementation on cardiovascular outcomes in individuals with low calcium intake in real-world settings. This study examined the association between calcium supplementation and cardiovascular outcomes in the Korean population in a real-world setting. This large retrospective cohort study included patients aged ≥45 years first prescribed calcium supplements in 2010. Age- and sex-matched controls were recruited among those who had no prescription for calcium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…The only nutrient found to be lacking when completely eliminating animal products is vitamin B12 that may require supplementation ( 33 ). Another nutrient that may need to be taken into consideration is calcium, but supplementation is not advisable because of its harmful effects, i.e., increased risk of CVDs ( 34 ). Interestingly, a study demonstrated that, despite the calcium level dropping at 3 weeks, it appears to rise after 6 weeks of adhering to a healthy PBD ( 33 ).…”
Section: What Are Pbds?mentioning
confidence: 99%
“…The only nutrient found to be lacking when completely eliminating animal products is vitamin B12 that may require supplementation ( 33 ). Another nutrient that may need to be taken into consideration is calcium, but supplementation is not advisable because of its harmful effects, i.e., increased risk of CVDs ( 34 ). Interestingly, a study demonstrated that, despite the calcium level dropping at 3 weeks, it appears to rise after 6 weeks of adhering to a healthy PBD ( 33 ).…”
Section: What Are Pbds?mentioning
confidence: 99%
“…Some studies in the past showed that either too high or too low levels of 25(OH)D could cause a poor prognosis [110,111], but subsequent studies found no definite correlation between 25(OH)D levels and outcome [112,113]. More research indicates that raising calcium levels in the blood as a result of vitamin D supplementation may be the main cause of the poor prognosis [114][115][116][117][118]. Additionally, a previous study recommended that vitamin K2 could assist in putting calcium in the hard tissues rather than the soft tissues, minimizing the likelihood of calcium-related side effects [119].…”
Section: Side Effects Of Excess Vitamin Dmentioning
confidence: 99%
“…Also, the possible adverse events outweigh the possible benefits of such supplementation [40]. A study by Park et al on a Korean population investigated the association between calcium supplementation and cardiovascular outcomes and showed that the cumulative incidence of acute myocardial infarction, ischemic stroke, and death was significantly higher in the calcium supplementation group than in the control group [41]. These findings were confirmed by the Women's Health Initiative Calcium/Vitamin D Supplementation Study, which showed that calcium supplements with or without vitamin D modestly increased the risk of cardiovascular events, especially myocardial infarction in women [42].…”
Section: Discussionmentioning
confidence: 99%